The Neurostimulation Appropriateness Consensus Committee (NACC) Recommendations for Infection Prevention and Management. Issue 1 (2nd January 2017) - Deer, Timothy R.; Provenzano, David A.; Hanes, Michael; Pope, Jason E.; Thomson, Simon J.; Russo, Marc A.; McJunkin, Tory; Saulino, Michael; Raso, Louis J.; Lad, Shivanand P.; Narouze, Samer; Falowski, Steven M.; et al.
Abstract : Introduction: The use of neurostimulation for pain has been an established therapy for many decades and is a major tool in the arsenal to treat neuropathic pain syndromes. Level I evidence has recently been presented to substantiate the therapy, but this is balanced against the risk of complications of an interventional technique. Methods: The Neurostimulation Appropriateness Consensus Committee (NACC) of the International Neuromodulation Society convened an international panel of well published and diverse physicians to examine the best practices for infection mitigation and management in patients undergoing neurostimulation. The NACC recommendations are based on evidence scoring and peer‐reviewed literature. Where evidence is lacking the panel added expert opinion to establish recommendations. Results: The NACC has made recommendations to improve care by reducing infection and managing this complication when it occurs. These evidence‐based recommendations should be considered best practices in the clinical implantation of neurostimulation devices. Conclusion: Adhering to established standards can improve patient care and reduce the morbidity and mortality of infectious complications in patients receiving neurostimulation.